Ectomycorrhizal fungal diversity decreases in Mediterranean pine forests adapted to recurrent fires. Issue 13 (20th June 2020) - Pérez‐Izquierdo, Leticia; Zabal‐Aguirre, Mario; Verdú, Miguel; Buée, Marc; Rincón, Ana
Abstract: Fire is a major disturbance linked to the evolutionary history and climate of Mediterranean ecosystems, where the vegetation has evolved fire‐adaptive traits (e.g., serotiny in pines). In Mediterranean forests, mutualistic feedbacks between trees and ectomycorrhizal (ECM) fungi, essential for ecosystem dynamics, might be shaped by recurrent fires. We tested how the structure and function of ECM fungal communities of Pinus pinaster and Pinus halepensis vary among populations subjected to high and low fire recurrence in Mediterranean ecosystems, and analysed the relative contribution of environmental (climate, soil properties) and tree‐mediated (serotiny) factors. For both pines, local and regional ECM fungal diversity were lower in areas of high than low fire recurrence, although certain fungal species were favoured in the former. A general decline of ECM root‐tip enzymatic activity for P. pinaster was associated with high fire recurrence, but not for P. halepensis . Fire recurrence and fire‐related factors such as climate, soil properties or tree phenotype explained these results. In addition to the main influence of climate, the tree fire‐adaptive trait serotiny recovered a great portion of the variation in structure and function of ECM fungal communities associated with fire recurrence. Edaphic conditions (especially pH, tightly linked to bedrock type) were an important driver shaping ECM fungal communities, but mainly at the local scale and probably independently of the fire recurrence. Our results show that ECM fungal community shifts are associated with fire recurrence in fire‐prone dry Mediterranean forests, and reveal complex feedbacks among trees, mutualistic fungi and the surrounding environment in these ecosystems.